EL SISTEMA GENERAL DE REGALÍAS COMO INSTRUMENTO DE EQUIDAD TERRITORIAL EN COLOMBIA (2016)
This article aims to analyse the equity territory in Colombia generated as result of the expedition of the 05 legislative act of 2011 that created the General System of Regalías - GSR-, formed by the set of income derived from the exploitation of nonrenewable natural resources, together with the mappings, entities, procedures and regulations of such income, reform carried out in response to the economic boom that had been generated at that time as a result of mining productivity - energy of the country and supported on four principles: saving for the future; regional, social and equity between generations; regional competitiveness and good governance, whose development took place through the Law 1530 of 2012.